Housing for disabled people: what do they need? - Ab Rahman, Syakir Amir; Samsudin, Nasriah; Mohamed Osman, Mariana; Bachok, Syahriah; Rabe, Noor Suzilawati (Malaysian Institute of Planners, 2018)
Across the world, people with disabilities, advocacy companies, key non-authorities and government stakeholders are trying to find approaches to enhance housing assist preparations for the disabled people. In order to do so, the housing industry should be more adaptive to meet the demand of the people with special needs. The government also needs to plan for suitable housing policies for all groups of people. Housing is the central focus for human being including the disabled people and houses that follow housing standard for the disabled will improve their quality of life. The objective of this paper is to study the preferences in terms of price, location and design factors in owning a residential property among the disabled community in Kuala Lumpur and Selangor. A survey questionnaires was distributed to 400 respondents of the disabled community. The survey focused on two categories of disability, which are the physical disability and visual impairment. The outcome of this study describes the preferences in owning a residential property in term of price, location and design of the property. Recommendation was then made on housing strategy in planning for the price, location and design of residential property for the disabled community in Kuala Lumpur and Selangor.